Interaction between water, crop residue and fertilization management on the source-differentiated nitrogen uptake by rice - Andrea Vitali; Federica Russo; Barbara Moretti; Marco Romani; Francesco Vidotto; Silvia Fogliatto; Luisella Celi; Daniel Said-Pullicino (Biology and Fertility of Soils, 2024)
Alternate wetting and drying (AWD) is an effective water-saving practice for rice cultivation that may however promote nitrogen (N) losses compared to continuous flooding (CF). The interaction between water, crop residue and N fertilization management can influence the contribution of different N sources to plant uptake. We hypothesized that microbial processes driving the source-differentiated N supply for rice uptake during the early growth stages will depend on the interaction between water management, the timing of straw incorporation with respect to flooding and the temporal distribution of mineral N application. Rice was grown for 60 days in mesocosm experiment involving a factorial design with (i) two water regimes (CF vs. AWD) and (ii) three straw and fertilizer managements, during which soil N, porewater chemistry, plant growth and N uptake were evaluated. Source partitioning of plant N between fertilizer-, straw- and soil-derived N was achieved by means of a dual-stable isotope 15 N tracing approach. Although AWD reduced total N uptake by about 4–25% with respect to CF, this could only be partly attributed to a lower uptake of fertilizer-N (and lower fertilizer-N use efficiency), suggesting that other N sources were affected by water management. Our findings evidence how the interaction between soil redox conditions and the availability of labile C and inorganic N strongly determined the supply of soil-derived N through microbial feedback and priming responses. Although incorporated straw contributed only minimally to rice N, it represented the primary driver controlling plant N nutrition through these microbial responses. These insights may contribute to identify suitable fertilization practices that favour plant N uptake during the early stages of rice growth under AWD.